Evaluasi Pencahayaan Alami pada Bangunan Indekos: Studi Kasus Kos Kita di Kota Kendari - Mustakima, D.B.; Gamalia, A. Nurul; Tamimi, N.; Cahyani, Cahyani (JURNAL RUANG / ISSN : 2085-6962, 2024)
Natural lighting is one of the design aspects that needs attention because it greatly affects the comfort of a space and energy usage. Boarding houses are a type of residential function that faces challenges, especially during the Covid pandemic, which forced residents to stay in their rooms while still being energy efficient. Optimal use of daylight is a middle ground to address these two major challenges faced by architects today. The purpose of this paper is to evaluate the design of boarding houses that have been built, particularly those located in Kendari city. The results show that the natural lighting in these boarding houses does not meet the standards and needs to increase its dimensions by 420% from the original size. This result will later serve as a consideration for designers, especially owners, when planning renovations